Effect of Perceived Authenticity on [Kick A Goal] Female Viewers' Football Participation Intention : The Mediating role of Viewing Flow - Hyunjee Rhee; Eunah Hong (Korea Institute of Sport Science, 2024)
PURPOSE This study aims to examine the mediating effect of viewing flow on the relationship between perceived authenticity among [Kick A Goal] female viewers' and football participation intention. METHODS A total of 414 questionnaires were distributed to [Kick A Goal] female viewers, aged from 20s to 60s, who had no experience in football. Among the collected questionnaires, the data used for the final analysis was 338 after data cleaning. The data analysis was conducted using SPSS 25.0, and it included frequency analysis, descriptive statistics analysis, correlation analysis, simple regression analysis, and a three-step mediation analysis proposed by Baron & Kenny(1986). RESULTS This study's results were as follows: First, the perceived authenticity of female viewers positively affected viewing flow. Second, the viewing flow of female viewers positively affected their football participation intention. Third, viewing flow fully mediated the relationship between perceived authenticity and football participation intention. CONCLUSIONS In summary, this study suggests that it is significant to produce programs with authenticity and maximize viewing flow to further enhance the intention of female viewers to participate in football.